PENERAPAN TIME DRIVEN ACTIVITY BASED COSTING PADA BIAYA RAWAT INAP DI RS DARUS SYIFA SURABAYA: Cost of Hospitalization, Inpatient, Installation Time Driven Activity Based Costing (TDABC) - Pramitasari, Dini Ayu (GEMA EKONOMI, 2021)
The hospital was established with the aim of providing the best health services for patients so that the management needs to provide good services in accordance with the rates charged to patients. Accurate cost calculation is very important done by the hospital management in the determination of the rates that hospitals do not too high which will overload the patient and not too low that will affect the profitability of home sick. An accurate determination of the tariffs would also be useful to cover all operating costs that have been incurred by the hospital. This research was conducted with the aim of studying the process of developing a method of Time-Driven Activity Based Costing (TDABC) in calculating the cost of inpatient care in Inpatient RS Darus Syifa Surabaya Installation. Research done by qualitative approaches with the methodology of the case study that is eksploratoris. Data collection is carried out by means of interviews, observations and documentation directly. Calculation of rates of hospitalization for each type of room according to the calculation method with TDABC higher if compared with the calculation done by the hospital management. Whereas the calculation of the Cost of Performing TDABC Activities can note that inpatient services only absorb about 3%-6% of the total capacity.